Proses Pemecahan Masalah Aritmetika Siswa Disabilitas - Ovan ovan Ovan (Universitas Andi Djemma, 2022)
This article aims to describe the process of solving arithmetic problems for students with disabilities. The research method used in this study is the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate, and interpret all available research with topic areas of interest. Data collection is done by documenting and reviewing all articles related to solving arithmetic problems. The articles used were 5 articles. The results showed that the process of solving arithmetic problems for students with disabilities was different. Students with disabilities experience many obstacles in solving arithmetic problems, especially in counting numbers from 10 to 100. Students with disabilities have difficulty understanding language. At other times, students with disabilities use procedures, strategies, and the desire to be active in the learning process. It is recommended for further researchers to develop special tools for students with disabilities.